2017
DOI: 10.1007/s00294-017-0769-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of yeast m6A methyltransferase in peroxisomal fatty acid oxidation

Abstract: The precise and controlled regulation of gene expression at transcriptional and post-transcriptional levels is crucial for the eukaryotic cell survival and functions. In eukaryotes, more than 100 types of post-transcriptional RNA modifications have been identified. The N-methyladenosine (mA) modification in mRNA is among the most common post-transcriptional RNA modifications known in eukaryotic organisms, and the mA RNA modification can regulate gene expression. The role of yeast mA methyltransferase (Ime4) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Blood cholesterol is one of the most important heritable risk factors for CAD, and is positively associated with mortality due to CAD ( 132 ). The role of m 6 A modification in lipid metabolism has been reported ( 133 ). Mo et al ( 121 ) investigated the effect of m 6 A-SNPs on lipid levels using GWAS summary datasets of 188,578 individuals.…”
Section: M 6 a And Cardiovascular Diseasementioning
confidence: 99%
“…Blood cholesterol is one of the most important heritable risk factors for CAD, and is positively associated with mortality due to CAD ( 132 ). The role of m 6 A modification in lipid metabolism has been reported ( 133 ). Mo et al ( 121 ) investigated the effect of m 6 A-SNPs on lipid levels using GWAS summary datasets of 188,578 individuals.…”
Section: M 6 a And Cardiovascular Diseasementioning
confidence: 99%
“…Additionally, Yadav et al . reported that IME4 gene played a role in the peroxisomal biogenesis, and IME4 gene loss also resulted in the peroxisomal malfunction of fatty acid oxidation 73 .…”
Section: Role Of M6a Modification In Lipid Metabolismmentioning
confidence: 99%
“…This study provides a basis for exploring the role of m 6 A methylation in peroxisomal biology (Table 3). 85…”
Section: Role Of M 6 a Modification In Lipid Metabolism-related Diseasesmentioning
confidence: 99%